BOOSTING STUDENT PURCHASING INTENTION: THE ROLE OF INSTAGRAM MARKETING, HALAL AWARENESS, AND PRODUCT QUALITY FOR MOCHIBO - Rismaningsih, Siswi; Kosim, Ahmad Mulyadi; Dewi, Reni Sinta (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
The objective of this study is to examine the impact of Instagram digital marketing, halal awareness, and product quality on the purchasing behavior of students at MSMEs Mochibo. This study employs a form of quantitative research. A non-probability sampling technique was employed to collect data from a sample of 101 respondents. A data collection technique was employed through the distribution of questionnaires. The data analysis technique employed includes classical assumption testing, multiple regression, hypothesis testing (t-test and F test), and the coefficient of determination. The data processing involves the utilization of SPSS software, specifically version 26. The findings of this study suggest that Instagram digital marketing has a notable impact on student buying interest at MSMEs Mochibo. However, the study did not find any significant effect of halal awareness on student buying interest at MSMEs Mochibo. Additionally, the studyfound that product quality has a significant influence on student buying interest at MSMEs Mochibo. This study aims to enhance students' understanding of halal practices and their impact on consumer behavior. Specifically, it focuses on how the message conveyed can influence students' buying interest in Mochibo MSMEs.